Dances with Sheep: On RePairing the Human–Nature Condition in Felt Thinking and Moving towards Wellbeing - Dako, Anna (Intellect Books, 2023)
Dances with Sheep presents the methodology of Felt Thinking in Movement as an eco-somatic practice inspired by re-thinking nature of being human, as well as contextualises it within wider frameworks of cultural, philosophical and therapeutic viewpoints on wellbeing. Felt Thinking is a self-inquiry practice grounded in somatic movement experience that originates in site-specific and embodied dialoguing between what is felt and what shapes as a responsive thought, as creative movement itself, and which paths ways for ecologically inclusive care for being well with self and other. The book elaborates on creative processes in and with the natural environment in relation to the movers' overall wellbeing and covers creative journeys of opening up to the living agency of Nature itself through the emergent three phases of experiential relatedness in embodied experience of the self. The book presents its original contribution to eco-phenomenology with its ontological principle of embodied relationality in towards and away from movement as a primal gateway to wellbeing and its creative inter-constitution. An intriguing and inspiring resource for students, practitioners, educators, self-learners, therapists and researchers. Foreword by Sondra Fraleigh.